أثر ضغوط الدور على الرضا الوظيفي دراسة ميدانية على المستشفيات الحكومية في محافظة حلب - الخشروم, محمّد مصطفى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة مصادر ضغوط الدور الوظيفي الناتجة عن: (صراع الدور، غموض الدور، عبء الدور الزائد) التي تواجه العاملين في مستشفى الباب الوطني، ودراسة درجات الرضا الوظيفي لهؤلاء العاملين، ومعرفة مدى وجود تأثير لمصادر ضغوط الدور على الرضا الوظيفي، والعلاقة بينهما وبين بعض المتغيرات الديموغرافية. تم تطبيق هذه الدراسة على عينة تعدادها (122) فرداً يعملون في مستشفى الباب الوطني من أربعة تخصصات وظيفية هي: (الأطباء، الإداريين، الممرضين، الفنيين) وتوصل البحث إلى أنّ أكثر مصادر ضغوط الدور وجوداً لدى العاملين بالمستشفى هو: صراع الدور، يليه غموض الدور، وأخيراً عبء الدور الزائد، كما أظهرت النتائج أن غموض الدور يؤثر تأثيراً عكسياً في الرضا الوظيفي، في حين أن كلاً من صراع الدور وعبء الدور الزائد لا يؤثران تأثيراً معنوياً في الرضا الوظيفي، وتبين أيضاً وجود اختلافات جوهرية في مستويات ضغوط الدور والرضا الوظيفي وفقاً لعدد من المتغيرات الديموغرافية. This search aims to study sources of role stress (role conflict, role ambiguity, role overload) which face workers in National Albab Hospital, and studying degrees of job satisfaction to this workers, And examine the impact the sources of role stress with the job satisfaction, and the relation between some demographic variables, The study was applied on sample examine (122) persons which work in National Albab Hospital (doctors, administrators, the nurses, and technical). The results of the study can be summarized as follows: More sources of role stress presence is role conflict, then role ambiguity ,and last the role overload, and role ambiguity adversely affect in job satisfaction, While there are no significant effect between role conflict, role overload and job satisfaction. Significant differences in role stress and job satisfaction were found according to several demographic variables.